APLIKASI PENUNTUN PELAKSANAAAN IBADAH PUASA RAMADHAN BERBASIS ANDROID - Maharani Cantika Cahyani; Darsono Nababan; Risald Risald (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2022)
Since Allah's command is only contingent upon a specific set of intents and conditions, fasting during Ramadan entails abstaining from anything that is prohibited from sunrise to sunset. assisting Muslims in performing their religious duties during the month of Ramadan so they can learn about any advice or knowledge regarding fasting during the entire month of Ramadan and determine if the advice or knowledge agrees with the genuine teachings of Islam or not. During the month of Ramadan, when fasting is required, the public will consult religious authorities for advice and information on a variety of topics. Worship is less than ideal due to the absence of mosques in existence, the limited time and location for meetings with religious authorities, and other factors. The research approach used in this study is the Mobile-D method, which is a branch of development based on mobile-based software. The outcomes of this research are an Android-Based Ramadan Fasting Implementation Guide Application, which can make it simpler for Muslims to access information about Ramadan fasting, Eid, zakat fitrah guidelines, Ramadan sunnah prayers, fasting schedule guides, and prayers during the month of Ramadan with the application developed by this author.